Using Anti-Nuclear Antibody and Rheumatoid Factor to Evaluation of Immune- Pathogenic Link of Rheumatoid Arthritis and Hepatitis C Virus in Iraqi Patients - Saleh, Mohammed A (Al-Nahrain Journal of Science, 2012)
This study was aimed to assess immune- pathogenic association of HCV infection among RA patients. A cross sectional study was conducted on the following groups: patient group includes forty patients with RA. Their age range was between (20-70) years with (7) (17.5%) males and (33) (82.5%) females. Healthy Group: thirteen serum samples were collected from apparently healthy individuals they served as a control group.Their age range was between (23-59) years. Results of this study reveals that the majority of RA patients are females (82,5 %) with females to males ratio of 4.7: 1. Moreover, the mean of age for RA and control groups are (46.83 ± 12.06) and (45.23 ± 12.58), respectively. The prevalence of RA among RA females was (82.5%) and (17.5%) for male and the frequency of rheumatoid Factor positivity among RA patients was (70%) in comparison with (0.0%) for apparently healthy control group with significant differences (P ≤ 0.001). Also, ANA positivity was higher (27,5%) than that for healthy control group (0.0%) with significant differences (P≤ 0.005). Results showed that, the frequency of positivity anti-HCV Ab was (5%) among RA patients in comparison with apparently healthy control group (0 %). Our results sustain the possible contribution of HCV infection in the pathogenesis of RA.